Content Analysis of Evidence-Based Articles in The Journal of Special Education. (February 2019) - Fisher, Larry B.; Spooner, Fred; Algozzine, Bob; Anderson, Kelly M.; Brosh, Chelsi R.; Robertson, Colleen E.
Conducting and supporting scientifically valid research activities and implementing evidence-based practices have driven recent hopes and efforts to achieve better outcomes for all students. In the context of ongoing internal review and continuous improvement, we were interested in how this evolution was reflected in empirical studies published in The Journal of Special Education ( JSE ). We coded key variables related to evidence-based research in articles published between 2004 and 2017. We found that most studies included elementary- or secondary-aged students with disabilities in general or special education classroom settings with teachers or researchers assessing the benefits of academic skill training interventions using single-case designs. We discuss implications for ongoing internal reviews and assessments as well as for comparisons, benchmarking, and evaluations within the field.